2017
DOI: 10.1590/1982-0194201700007
|View full text |Cite
|
Sign up to set email alerts
|

Sintomas depressivos na gestação e fatores associados: estudo longitudinal

Abstract: Objective: To identify the frequency of depressive symptoms during pregnancy and verify their association with sociodemographic, obstetric and health variables. Methods: A longitudinal study conducted with 272 pregnant women in 12 health units in the city of São Paulo. Data were obtained using a form for the independent variables, and the Edinburgh Postpartum Depression Scale applied at the 20 th , 28 th and 36 th gestational weeks. A model of generalized estimating equations was used to evaluate the associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
44

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(65 citation statements)
references
References 25 publications
(38 reference statements)
2
19
0
44
Order By: Relevance
“…No tocante aos determinantes intermediários, quanto ao nível educacional, sabe-se que gestantes com maior escolaridade apresentam menor chance de desenvolver sintomas depressivos (17) , sendo considerado um fator de proteção à sua saúde. Em contrapartida, o baixo nível de escolaridade é uma barreira para o acesso a informações e é um preditor significativo de mortalidade (18) .…”
Section: Discussionunclassified
“…No tocante aos determinantes intermediários, quanto ao nível educacional, sabe-se que gestantes com maior escolaridade apresentam menor chance de desenvolver sintomas depressivos (17) , sendo considerado um fator de proteção à sua saúde. Em contrapartida, o baixo nível de escolaridade é uma barreira para o acesso a informações e é um preditor significativo de mortalidade (18) .…”
Section: Discussionunclassified
“…18 A longitudinal study conducted with 272 pregnant women to identify the frequency of depressive symptoms during pregnancy and to determine its association with sociodemographic, obstetric and health variables revealed that psychological violence was a risk factor for the presence of depressive symptoms during pregnancy and for postpartum depression symptoms when the main aggressors were the partner and family members. 19 However, it is important to point out that psychological violence is often unnoticed at the health services, therefore it is the less considered than the other types of violent acts. Thus, the high prevalence detected is important to sensitize health professionals, managers and researchers, as well as the victims themselves, for this type of violence and its negative repercussions on women's health, specifically regarding their mental health.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to emphasize the importance of the professionals to direct their attention to the complaints of these mothers, without trivializing them, involving them with positive thoughts in the attempt to reduce their anguish of childbirth, increasing maternal-fetal attachment and; when it deems necessary, to request support from specialized mental health professionals (Lima et al, 2017).…”
Section: Treatmentmentioning
confidence: 99%